Horizontal gene transfer in plant microbiomes: integrons as hotspots for cross-species gene exchange - Ghaly, Timothy M.; Gillings, Michael R.; Rajabal, Vaheesan; Paulsen, Ian T.; Tetu, Sasha G. (Frontiers in Microbiology, 2024)
Plant microbiomes play important roles in plant health and fitness. Bacterial horizontal gene transfer (HGT) can influence plant health outcomes, driving the spread of both plant growthpromoting and phytopathogenic traits. However, community dynamics, including the range of genetic elements and bacteria involved in this process are still poorly understood. Integrons are genetic elements recently shown to be abundant in plant microbiomes, and are associated with HGT across broad phylogenetic boundaries. They facilitate the spread of gene cassettes, small mobile elements that collectively confer a diverse suite of adaptive functions. Here, we analysed 5,565 plant-associated bacterial genomes to investigate the prevalence and functional diversity of integrons in this niche. We found that integrons are particularly abundant in the genomes of Pseudomonadales, Burkholderiales, and Xanthomonadales. In total, we detected nearly 9,000 gene cassettes, and found that many could be involved in plant growth promotion or phytopathogenicity, suggesting that integrons might play a role in bacterial mutualistic or pathogenic lifestyles. The rhizosphere was enriched in cassettes involved in the transport and metabolism of diverse substrates, suggesting that they may aid in adaptation to this environment, which is rich in root exudates. We also found that integrons facilitate cross-species HGT, which is particularly enhanced in the phyllosphere. This finding may provide an ideal opportunity to promote plant growth by fostering the spread of genes cassettes relevant to leaf health. Together, our findings suggest that integrons are important elements in plant microbiomes that drive HGT, and have the potential to facilitate plant host adaptation.